(untitled) (Scottish Archaeological Internet Reports, 2009)
The charcoal reflects the successive accumulation of debris from small open fires which were located close to midden deposits and used for a range of activities including food processing. The wood used to fuel these fires was most probably collected as deadwood and included poor as well as good fuel woods. The range of wood identified and the proportional representation of each taxon is consistent throughout the site, with only minor variations, irrespective of the nature of each context. This is thought to reflect the short time that the site was in active use, the low diversity of the contemporary woody flora from which the wood originated, and the opportunistic exploitation of deadwood resources. Open woodland dominated by mixed birch/pine and hazel communities probably constituted the principal form of vegetation and this is supported by work on the vegetation of the area today.